Synergistic Response Of Pogostemon Cablin (Blanco) Benth. Cell Suspension Cultures To Precursor Feeding And Elicitation Towards The Production Of Patchoulol - Mazlan, Fatin Izzatie (2018)
Secondary metabolites in Pogostemon cablin (Blanco) Benth, especially patchoulolis known to possess strong neuroprotective activities, abilities for cognition enhancement as well as learning impairment attenuation. It was also proven to weakly inhibit replication of influenza B in vitro and provide the major constituents for perfumery industry. However, patchoulol content in a field planted P. cablin is very low and therefore higher volume of P. cablin plant supply is needed to fulfillthe increasing demand for this active compound. The main aim of this research done was to effectively increase the production of patchoulol in vitro using plant cell culture technique via precursor feeding and elicitation using biotic and abiotic elicitors as well as by combining the best from each of the abiotic and biotic elicitor with precursor. The initial work involved the plantlet regeneration of P. cablin as well as sub-culturing the 4 years old callus obtained from previous studies. The cell suspension cultures were established using the four years old callus and was maintained in MS media containing 1 mg/L picloram and incubated in total darkness. This process is necessary in order to produce a continuous supply of plant materials for further manipulation. Various types of abiotic (methyl jasmonate and chitosan) and biotic (yeast extract and Pycnoporus sanguineus) elicitors with different concentrations were studied in order to produce a higher yield of patchoulol in P. cablin cell suspension cultures. Elicitation with abiotic elicitors namely methyl jasmonate (MeJa; 50 µM) on day 10 corresponding to the stationary phase of cell growth yield the highest content of patchoulol (55.87 ± 2.03 µg/g) when the cultures were harvested on day 3 after MeJa addition. In the case of biotic elicitors, yeast extract (YE) with the concentration of 2 g/L was chosen as the best biotic elicitors responsible to increase patchoulol content in P. cablin cell suspension cultures. The effect of the stage growth cycle and duration of elicitor exposure suggest that MeJa (50 µM) treatment on the early exponential phase (day 4) yield the highest production of patchoulol when harvested on the 5th day (7.60 ± 0.04 µg/g). Meanwhile, YE that was elicited on the same growth phase and harvested on the same day as MeJa was capable to yield only 0.15 ± 0.06 µg/g patchoulol. A synergistic effect between trans, trans-farnesol (100 mg/L) as a precursor with 50 µM MeJa yield a negative effect in which combination of them shows a decrement of 0.88 folds of patchoulol production compared to the individually elicited groups. The same effect can also be seen when trans, trans-farnesol were added with YE (2 g/L). In conclusion, only the individually elicited cell suspension cultures of P. cablin is capable in improving the yield of patchoulol.